Gastrointestinal helminth fauna of zoonotic importance and pathological aspects in rodents (Rattus spp) in three environments - Abad A., Deisy (2017)
The study aimed to identify and determine the prevalence of zoonotic gastrointestinal helminths present in rodents (Rattus spp) in three environments (pig farms, zoo and food markets) of Lima, Peru and estimate the association between the presence of helminths and the variables place of origin, species, age and sex. A total of 245 rodents (Rattus rattus and Rattus norvergicus) were captured alive using live trap cages and were subsequently euthanized. Skulls, skin, teeth and morphometric parameters were used for taxonomic classification of species. Stomach and small and large intestine were collected. The helminths found were placed in 70% alcohol and selected tissues were preserved in 10% formalin. The prevalence of gastrointestinal helminths in rats was 72.2% whereas the prevalence of zoonotic helminth was 46.5%. Four species of zoonotic importance were found: Raillietina demerariensis, Gongylonema neoplasticum, Hymenolepis diminuta and Moniliformis moniliformis, where the latter two were more frequent in the three ecosystems. Other helminths identified were Mastophorus muris, Heterakis spumosa, Aspicularis tetrapera, Syphacia muris, Trichuris muris, Capillaria sp and Vampirolepis fraterna. The histopathological findings included a decrease in size of the villi, detachment of epithelial cells, increased numbers of goblet cells and enterocytes with eosinophils, lymphocytes, plasma cells and macrophages associated with H. diminuta, M. moniliformis and R. demerariensis.